Emergence of extensive multidrug-resistant Staphylococcus aureus carrying novel Sa-MRRlsa(E) in retail food - Shi Wu; Jiahui Huang; Feng Zhang; Jumei Zhang; Runshi Yang; Rui Pang; Jingsha Dai; Dongli Rong; Miao Zhao; Juan Wang; Yu Ding; Moutong Chen; et al. (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: The aim of this study was to investigate the prevalence and genetic environment of the multidrug resistance gene lsa(E) in food-related Staphyloccocus aureus in China. Methods: 1463 S. aureus from retail food products in 39 Chinese cities were investigated to determine the prevalence of lsa(E). Furthermore, antimicrobial susceptibility testing, whole-genome sequencing (WGS), and complete genetic analysis were performed in lsa(E)-positive isolates. Results: Thirty-five isolates (2.4%) were positive for the lsa(E) gene, which had an extensive multidrug-resistance phenotype. ST9-t899 and ST1-t4792 were the common sequence types in positive strains. The lsa(E) genes were located in two different types of novel multidrug resistance region (MRRlsa[E]) on the chromosome. The Sa-MRRlsa(E)-I were inserted into the lctP gene. The Sa-MRRlsa(E)-II were inserted into the crtP gene, and were comprised of seven antibiotic resistance genes (ARGs) interspersed with varieties of insertion sequences (ISs), transposons, and DNA invertase genes, showing a novel arrangement harboring lsa(E). Part of transposon Tn1546 was inserted downstream of lnu(B) in the novel Sa-MRRlsa(E)-II. Both types of Sa-MRRlsa(E) could be excised from the chromosome, indicating that Sa-MRRlsa(E) may be transferable. Conclusion: Our study is the first systematical investigation of lsa(E)-positive S. aureus in retail foods in China. It indicated that the origin of most food-related lsa(E)-positive S. aureus in China might be associated with livestock or poultry breeding farms, and these strains may be transmitted between animals and food. S. aureus carrying novel Sa-MRRlsa(E), especially, serve as reservoirs of antibiotic resistance traits, and warrant further attention.